Rising importance of agricultural nitrogen oxide emissions in China’s future PM2.5 pollution mitigation - Yuanhong Zhao; Zhanpeng Su; Youfan Chen; Suyi Hou; Xiao Lu; Bo Zheng; Lei Liu; Yuepeng Pan; Wen Xu; Xuejun Liu; Lin Zhang (npj Climate and Atmospheric Science)
Abstract Controlling ammonia (NH3) emissions through agricultural management has been recognized as effectively mitigating fine particulate matter (PM2.5) pollution in eastern China. However, agricultural nitrogen oxide (NOx) emissions are often overlooked. Here we estimate agricultural NOx emissions and design a set of atmospheric chemistry model experiments to assess their role in present and future PM2.5 pollution mitigation in eastern China. The results show that when fossil fuel emissions decrease to 2060 levels, the contribution of agricultural NOx emissions to secondary inorganic aerosol (SIA) concentrations during the crop-growing season will reach 40% over intensive agricultural areas such as North China Plain, and the efficiency of reducing agricultural NOx emissions in mitigating SIAs will become comparable to reducing NH3 emissions. By estimating the optimal reactive nitrogen (Nr) emission control pathway, we find that when including agricultural NOx emissions, the strategies will shift in favor of controlling agricultural Nr emissions to achieve more efficient PM2.5 mitigation. Such additional benefits of agricultural nitrogen management should be considered when designing future air quality strategies for agricultural-intensive regions.